What's new about the new public management? Administrative change in the human services - Page, Stephen (2005)
Interpretations of the emergence of the New Public Management are split. The champions of the movement present it as a new administrative paradigm that departs sharply from past thinking and practice, whereas skeptics argue it has evolved incrementally from post administrative traditions. To assess these views, this article examines recent administrative innovations in the human services that broadly reflect the New Public Management. The findings suggest that these innovations have built incrementally on past reforms in the human services field, supporting the skeptics' claim that the New Public Management reprsents on evolution and renewal of historical trends in public administration - Reproduced.
Keywords: Public administration